2008
DOI: 10.1111/j.1473-2165.2008.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study on patient response to botulinum toxin cosmetic therapy

Abstract: Our study correlated with previous studies done on retention rate of BTX cosmetic patients and satisfaction level on areas treated. The cost of BTX remained one of the primary concerns for repeat visits. Most patients were happy with their visits to the dermatology offices for BTX procedure, although things can be done to further enhance their visits and the likelihood that they will return.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…3 It was primarily found in adulterated meat products by causing botulism. Nowadays, BoNT is commonly used in medical applications to treat chronic myofascial pain, 4 headache, 5 urinary incontinence, 6 and hyperhidrosis 7 or in cosmetic applications 8,9 among others.…”
mentioning
confidence: 99%
“…3 It was primarily found in adulterated meat products by causing botulism. Nowadays, BoNT is commonly used in medical applications to treat chronic myofascial pain, 4 headache, 5 urinary incontinence, 6 and hyperhidrosis 7 or in cosmetic applications 8,9 among others.…”
mentioning
confidence: 99%
“…These findings are at odds with earlier studies performed more than 15 years ago, which reported high levels of satisfaction with botulinum toxin injections. 5,6 This may be for various reasons.…”
Section: Self-perception Of Natural Outcome Appearance and Emotional ...mentioning
confidence: 99%